Pore characteristics in biological soil crusts are independent of extracellular polymeric substances - Vincent, J. M. N. L. Felde; ROSSI, FEDERICO; Claudia, Colesie; Daniel, Uteau Puschmann; Rainer, Horn; Peter, Felix Henningsen; DE PHILIPPIS, ROBERTO; Stephan, Peth (Soil Biology and Biochemistry, 2016)
Biological soil crusts (biocrusts) are considered key players in hydrological cycles of many arid environments. The phototrophic organisms in these crusts excrete extracellular polymeric substances (EPSs), which bind soil particles together, thereby stabilizing the soil surface. In a previous work, the non-invasive extraction of EPSs in biocrusts resulted in a change of their hydrological behavior. As this was suspected to be the effect of a change in their pore structure, we employed high resolution X-ray micro tomography to investigate structural changes of biocrusts after EPS-extraction. We studied biocrusts from four different study sites in Svalbard, Germany, Israel and South Africa. Two different fractions of EPSs (tightly bound and colloidal) were extracted, using the same extraction method with two different solvents. Our results suggest that the extraction of EPSs did not result in structural differences at a resolution of 7 mu m. We therefore conclude that the previously observed change in hydrological behavior is likely to be the result of a change of the physico-chemical properties of the very surface of the crust, rather than of its inner structure.